P142 Role of e-health in the management of Inflammatory Bowel Disease: A systematic review and meta-analysis. (27th May 2021) - Kuriakose Kuzhiyanjal, A J; Nigam, G B; Antoniou, G A; Cross, R K; Farraye, F A; Limdi, J K
Abstract: Background: The increasing incidence and prevalence of inflammatory bowel disease (IBD), has fuelled the need for innovative models of care. We aimed to compare effectiveness of e-health interventions (virtual clinics, telephone consultation, remote monitoring or any web-based health platform) with standard care in management of IBD. Our primary outcomes were to assess the difference in disease activity and percentage of patients in clinical remission at the end of follow up. Our secondary outcomes were to investigate differences in quality of life (QoL), IBD-knowledge & rate ratios (RR) for endoscopic procedures, total healthcare encounters, corticosteroid use, and IBD related hospitalisation or surgery. Methods: We searched Medline, Embase, PubMed, CINAHL, PsychInfo, Clinical trials registry and Cochrane databases for randomised controlled trials (RCT) published in the English language until November 2020, comparing e-health interventions to standard care for patients with IBD. Pooled estimates of dichotomous outcomes were calculated using the odds ratio (OR) and 95% confidence interval (CI) using the Mantel-Haenszel statistical method. For continuous data, the standardised mean difference (SMD) and 95% CI were calculated using the inverse variance statistical method. Event data were analysed and expressed as RR with 95% CI using the inverse variance statistical method. Random effects model was used. Results: Nine studies involving 1841 participants (991 e-health group and 850 controls) were identified. There was no statistically significant difference between the mean disease activity scores for UC (SMD 0.22, 95% CI: -0.04–0.48) and CD (SMD 0.02, 95% CI: -0.18–0.22) in the e-health and standard care groups and no statistically significant difference in the percentage of patients in clinical remission at the end of follow up between both groups (OR -1.05, 95% CI: 0.76–1.45). Higher QoL (SMD 0.19, 95% CI: 0.05–0.34) and IBD knowledge (SMD 0.25, 95% CI: 0.12–0.37) scores were noted in the e-health group compared to standard care. There were no statistically significant differences noted in the RR for endoscopic procedures (RR 1.01, 95% CI: 0.81–1.26), total healthcare encounters (RR 1.03, 95% CI: 0.93–1.15;), IBD related, corticosteroid use (RR 0.99, 95% CI: 0.51–1.92), and IBD related hospitalisation (RR 0.81, 95% CI: 0.53–1.25) or surgery (RR 0.87, 95% CI: 0.49–1.55) between both groups. Conclusion: E-health interventions are comparable with standard care for impact on disease activity, remission, endoscopy utilisation, total healthcare encounters, corticosteroid use, and IBD related hospitalisation or surgery. QoL and IBD related knowledge were higher in the e-health compared to the standard care group.